Signature of ultrafast formation and annihilation of polaronic states in a layered ferromagnet - Yin, Tingting (2023)
The strong interaction between charge and lattice vibration gives rise to a polaron, which has a profound effect on optical and transport properties of matters. In magnetic materials, polarons are involved in spin dependent transport, which can be potentially tailored for spintronic and opto-spintronic device applications. Here, we identify the signature of ultrafast formation of polaronic states in CrBr3. The polaronic states are long-lived, having a lifetime on the time scale of nanoseconds to microseconds, which coincides with the emission lifetime of ∼4.3 μs. Transition of the polaronic states is strongly screened by the phonon, generating a redshift of the transition energy ∼0.2 eV. Moreover, energy-dependent localization of polaronic states is discovered followed by transport/annihilation properties. These results shed light on the nature of the polarons and their formation and transport dynamics in layered magnetic materials, which paves the way for the rational design of two-dimensional magnetic devices.